Dried distiller´s grains plus solubles supplementation improves low-quality tropical grass utilization on beef steers = Suplementação de grãos de destilação secos com solúveis melhora a utilização de grama tropical de baixa qualidade para novilhos de corte - Hernandez, Olegario; Lopez, Agustin; García, Elisa Mariana; Nazareno, Mónica Azucena; Arroquy, Jose Ignacio (Centro de Ciências Rurais, Universidade Federal de Santa Maria, 2023)
This study was designed to evaluate the effect of corn dried distiller´s grains (DDGS) supplementation on feed intake, total tract digestibility, and ruminal fermentation of beef steers fed low-quality Guinea grass (Megathyrsus maximus, cv. Gatton panic). Twelve Braford crossbred steers were housed in individual pens (n = 4 steers/treatment), provided with three levels of DDGS supplement: 0%, 0.6%, or 1.2% BW. Steers were blocked by live weight and randomly assigned to treatments within the block. Corn DDGS supplementation increased total OM intake (21.55, 40.23, and 56.69 g/kg BW0.75) and tract OM digestibility (46.33, 49.03, and 72.39 % DM). Total tract digestible OM, CP, NDF and EE intake also increase in response to DDGS supplementation. Forage OM intake decreased when supplementation level reached 1.2 % BW. Also, ruminal pH decreased with DDGS supplementation level (6.88, 6.47, and 6.27). No differences were observed in total volatile fatty acids (VFA) concentration; however, the molar proportion of acetate decreased (77.98, 73.90, and 67.29 % Total VFA) as well as acetate: propionate ratio (4.38, 3.48, and 2.74). On the contrary, propionate proportions increased (18.32, 21.86, and 24.81 % Total VFA). Levels of ammonia and lactate were within suggested values for optimal fermentation and bacterial growth. Low-quality grass supplementation with corn DDGS increased total OM intake and digestibility. Also, DDGS inclusion favorably altered volatile fatty acids profile by reducing the acetate to propionate ratio regarding forage-only diets.